Toward a new classification of planthoppers Hemiptera Fulgoromorpha: 2. Higher taxa, their names and their composition - Bourgoin, Thierry; Szwedo, Jacek (Zootaxa, 2023)
A synthesis of planthopper suprafamilial and familial classification is provided and discussed, solving some nomenclatural issues for the group, and adopting an enriched presentation with a clear distinction between the taxon name and its concept.